HUBUNGAN ANTARA MUTU PELAYANAN DENGAN KEPUASAN PASIEN DI KAMAR OBAT PUSKESMAS TOAYA KECAMATAN SINDUE KABUPATEN DONGGALA - David Restu Gunawan; I Kadek Wartana (Jurnal Ilmiah Kesmas -IJ, 2012)
In order to quality health services to achieve the desired goals are many things that must be met, namely service officer, the officer attitude, patient waiting times and patient satisfaction are the requirements to be met and be an important strategy that should not be ignored by policy makers in health. The purpose of this study was to determine the relationship between quality of care with the patient’s room satisfaction of health center drugs Toaya Donggala district. This type of study is analytical survey using cross sectional approach. Analysis of data using univariate and bivariate analysis. The number of samples in this study a ttotal of 61 respondents in which the samples used in this study were all patients who received care at the clinic drugs of Toaya Public Health Center when the study conducted by the sampling technique used was accidental sampling. The results showed tha there is a significant association between service officer with the patient satisfaction rate. Service officers have a good chance for 3 times to give satisfaction to the patient. There was a significant association between the attitude of officers to the level of patient satisfaction. Officers hace a good attitude as much as 14 times the chance to give satisfaction to patients. There wasn’t a significant association between waiting time with levels of patient satisfaction. By looking at the results of this study is expected that the dispensary staff at Toaya Public Health centers in order to improve the quality of health services so that patients were satisfied with the services provided.